ANALISIS WACANA KRITIS “CAKNUN ANTARA KPK DAN TEROR” DI CHANNEL YOUTUBE MATA NAJWA - A‟yun Masfupah (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
This study aims to explain the discourse contained in the May 4, 2019 edition of Mata Najwa with the theme